Feasibility analysis of implant movement along arc trajectory under non-contact control in magnetic stereotaxic system - Цзяо Ханкунь; Олег Аврунін (Сучасний стан наукових досліджень та технологій в промисловості)
In this paper, the non-contact control of magnetic implants by changing the external magnetic field in the magnetic stereotaxic system is introduced, and the feasibility of making them move along the arc trajectory is analyzed. Through COMSOL software, the process of moving the miniature magnetic implant along the arc trajectory was simulated, the change of the micro-magnetic implant trajectory after the external magnetic field was changed, the relative position relationship between the large permanent magnets was determined, and the mechanical analysis of the miniature magnetic implant moving along the arc trajectory was carried out. In this experiment, we fix a large permanent magnet, only move the second permanent magnet, first, observe the process of small permanent magnets moving along a straight trajectory, determine the position of the large permanent magnet magnetic field when it contacts the small permanent magnet, and then, analyze the force of the small permanent magnet through the force calculation module, and determine the relative position relationship between the two large permanent magnets by comparing  and , and when the small permanent magnet will start to move along the arc trajectory. Then, according to the previous data, we move two adjacent large permanent magnets at the same time at a certain interval, record the movement trajectory of the small magnet, Finally, with the force calculation module of the COMSOL software, force analysis of small permanent magnets moving along arc trajectories. The data from this experiment will be used to determine the relative position relationship between two large permanent magnets adjacent to each other during the actual experiment, and under what conditions the small permanent magnets will move along the arc trajectory. The purpose of this experiment is to provide theoretical and data support for the subsequent practical experiments of the magnetic stereotactic system, and all parameters in the COMSOL software are derived from the actual measurement data, so as to improve the reliability of the simulation results.